2009
DOI: 10.1590/s1415-98482009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Análise empírica da formação de expectativas de inflação no Brasil: uma aplicação de redes neurais artificiais a dados em painel

Abstract: O objetivo principal deste trabalho é estudar empiricamente o processo de formação de expectativas inflacionárias no Brasil, no período recente (pós-metas de inflação), através de um modelo conexionista, que aproxima a forma como os agentes fazem previsões. Os resultados obtidos permitem afirmar que a maior influência sobre as expectativas inflacionárias no período como um todo foi da volatilidade cambial, seguida pela variação no preço das commodities, pela defasagem de ordem um das expectativas, pela variaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Using the copula approach, Moreira et al (2013) analyzed the dependence between expected inflation and observed inflation in Brazil from January 2005 to June 2011. The results were consistent with other works such as Palma and Portugal (2009), as the dependence structure highlighted a weak relationship between expected and observed inflation, suggesting high monetary policy credibility in Brazil under the inflation-targeting regime.…”
Section: An Alternative Approachsupporting
confidence: 91%
“…Using the copula approach, Moreira et al (2013) analyzed the dependence between expected inflation and observed inflation in Brazil from January 2005 to June 2011. The results were consistent with other works such as Palma and Portugal (2009), as the dependence structure highlighted a weak relationship between expected and observed inflation, suggesting high monetary policy credibility in Brazil under the inflation-targeting regime.…”
Section: An Alternative Approachsupporting
confidence: 91%